2010
DOI: 10.1111/j.1743-6109.2010.01789.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tramadol on Demand Vs. Daily Paroxetine as a Long-Term Treatment of Lifelong Premature Ejaculation

Abstract: Introduction Premature ejaculation (PE) is the most common male sexual dysfunction with many lines of treatment that show conflicting results. Paroxetine and tramadol were both reported to be effective in treatment of PE. Aim To investigate the effectiveness of long-term daily paroxetine vs. on-demand tramadol HCl in treatment of PE. Main Outcome Measures Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 23 publications
1
56
0
2
Order By: Relevance
“…However, other researchers concluded that tramadol does not make as distinct a contribution to PE improvement as some proponents have suggested. The dissenting researchers have even questioned the safety of tramadol for PE, noting concerns such as severe SEs and potential drug dependence [12]. …”
Section: Introductionmentioning
confidence: 99%
“…However, other researchers concluded that tramadol does not make as distinct a contribution to PE improvement as some proponents have suggested. The dissenting researchers have even questioned the safety of tramadol for PE, noting concerns such as severe SEs and potential drug dependence [12]. …”
Section: Introductionmentioning
confidence: 99%
“…36,37 Other agents, including a-adrenoreceptor antagonists (terazosin and alfuzosin) 38 and an analgesic opioid receptor agonist and noradrenalin reuptake inhibitor (tramadol), have also been investigated for treating PE. 39 Psychotherapy and behavioural therapy also have a role, although well-designed, controlled trials that use such approaches are lacking. 40 PE management is dependent upon aetiology.…”
Section: Discussionmentioning
confidence: 99%
“…42 In an open-label crossover comparative study of daily paroxetine (20 mg) and on-demand tramadol (50 mg) in 35 subjects with lifelong PE, superior IELT fold increases and responses were demonstrated with paroxetine (22 fold vs. fivefold for tramadol) after 12 weeks of treatment. 39 Hellstrom 46 stated that tramadol for the treatment of PE showed promise, but the data available from small trials need to be corroborated. In addition, long-term studies are warranted to investigate the risk of opioid addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to stimulating the μ-receptor, tramadol acts as an inhibitor of norepinephrine and serotonin [30]. Though not as effective as paroxetine, researchers have reported beneficial results in head-to-head trials and have suggested tramadol as a possible on-demand treatment of PE [31].…”
Section: Opioid Agonistmentioning
confidence: 99%